Assessment of mastication in healthy children and children with cerebral palsy: a validity and consistency study. (28th February 2013) - Remijn, L.; Speyer, R.; Groen, B. E.; Holtus, P. C. M.; van, J.; Nijhuis‐van der, M. W. G.
Summary The aim of this study was to develop the Mastication Observation and Evaluation instrument for observing and assessing the chewing ability of children eating solid and lumpy foods. This study describes the process of item definition and item selection and reports the content validity, reproducibility and consistency of the instrument. In the developmental phase, 15 experienced speech therapists assessed item relevance and descriptions over three Delphi rounds. Potential items were selected based on the results from a literature review. At the initial Delphi round, 17 potential items were included. After three Delphi rounds, 14 items that regarded as providing distinctive value in assessment of mastication (consensus >75%) were included in the Mastication Observation and Evaluation instrument. To test item reproducibility and consistency, two experts and five students evaluated video recordings of 20 children (10 children with cerebral palsy aged 29–65 months and 10 healthy children aged 11–42 months) eating bread and a biscuit. Reproducibility was estimated by means of the intraclass correlation coefficient (ICC). With the exception of one item concerning chewing duration, all items showed good to excellent intra‐observer agreement (ICC students: 0·73–1·0). With the exception of chewing duration and number of swallows, inter‐observer agreement was fair to excellent for all items (ICC experts: 0·68–1·0 and ICC students: 0·42–1·0). Results indicate that this tool is a feasible instrument and could be used in clinical practice after further research is completed on the reliability of the tool.